Człowiek jako dynamiczna jednostka duchowo-cielesna w nauczaniu św. Maksyma Wyznawcy - Kashchuk, Oleksandr (Vox Patrum, 2015)
In St. Maximus the Confessor’s teaching human nature consists of the soul and the body, in which logos of power that unifies them together is inscribed. Human nature manifests itself in the individual human being. The human being as the body and the soul naturally longs for God. This longing is fulfilled by the movement, which is connected to dynamism of the entire human structure. The dynamism is inscribed in the mind, reason, spirit, will, sense, passionate powers and body. The dynamic aspiration for God does not imply getting rid of any of the human elements, even passionate and bodily, but on the contrary, it demands appreciation and proper use of all the natural powers of the human being. Maximus the Confessor treats the human being as a whole. The human is not only mind, reason and spirit, but also will, sense, passionate powers and body. The dynamism of mental and spiritual sphere should be extended in the senses, passionate powers and body, so that the body also becomes the source of virtues, and is deified together with the soul through unity with the Absolute. This unity as the goal of human longing will never be static, but dynamic, because the fulfillment of this longing is the state with eternal movement. So human being will constantly strive for even more perfect unity with God. Through this unity the human being becomes more human. The originality of the Author consists in the fact that using the anthropological views of the earlier tradition and interpreting them mystically and symbolically, he intertwined the entire dynamism of human being with the structure of the Platonic world. The human being through the longing for God and through the proper use of natural powers mystically unites with God not only himself/herself, but also the entire universe, because the structure of the human being is analogous to the structure of the universe.